Soil liquefaction potential assessment of ports in Odisha, India - Satyaprakash Mishra; Arjun Sil; Amit Kumar Das (Natural Hazards Research)
This study presents a comprehensive assessment of the liquefaction potential at three major port sites in Odisha, India, i.e., Dhamara, Paradeep, and Gopalpur, utilizing well-established methodologies. The evaluation was conducted under the framework of seismic hazard analysis, incorporating site-specific geotechnical data from Standard Penetration Test (SPT) boreholes and considering the maximum estimated earthquake scenarios. The seismic hazard analysis identified varying levels of Peak Ground Acceleration (PGA) across the port sites, with corresponding magnitudes of 7.4 and 6.5 for Dhamara, Paradeep, and Gopalpur, respectively. Liquefaction susceptibility was quantified using the Liquefaction Potential Index (LPI), revealing significant variability across the sites. The Gopalpur port site exhibited a very low to low liquefaction severity, indicating minimal risk under the assessed seismic conditions. In contrast, the Dhamara and Paradeep ports demonstrated a higher susceptibility, with two out of four borehole locations at each site showing high liquefaction severity. This elevated risk is primarily attributed to the presence of saturated silty fine sands in the upper soil layers, which are particularly prone to liquefaction. The findings underscore the critical need for targeted mitigation measures, including ground improvement techniques, at the Dhamara and Paradeep sites to enhance infrastructure stability and safety. The study provides valuable insights into the seismic risks associated with these coastal regions and offers a robust framework for future seismic risk assessments. The outcomes of this research are instrumental in informing the design and implementation of resilient infrastructure in Odisha, thereby contributing to the region's overall seismic safety and disaster preparedness.